The Paradox of the Neighborhood: The Hero Bellerophon in Early Christian Art from the 4th to the 6th Century - Suslenkov, Vitaly Ye. (Actual Problems of Theory and History of Art, 2024)
The article is devoted to the images of Bellerophon striking the Chimera, placed in a Christian context or correlated with it. The emphasis is put on the mosaics of the Roman Britannia (Hinton St. Mary, Frampton, Lallingstone) and Lusitania (Mertola). The images of Christ (Hinton St. Mary) or christograms (Lallingstone, Frampton) are placed side by side with the image of the pagan hero. Preserved during the conversion of the owners of the villa to Christianity, he could play a role in the symbolic reading of Christian ideas (Lallingstone), or was simultaneously related to the Christian complex and associated with it (Mertola). A possible Christianized interpretation of the image of Bellerophon is compared to the interpretations of Hercules, Orpheus, Odysseus, and other heroes treated in some Christian sources, whose images are also known in the art of the early Christian era. A comparison is made with ensembles with pagan heroes where the Christian idea is not expressed, but can also be read. The main features of the hero’s image, such as the ascension on a heavenly horse and the killing of a monstrous Chimera, make it a commentary on the “heroic” nature of Christ, and symbolize His property and the principle by which the mechanism of the universe is launched — victory over death, marked by material and spiritual evil.
Keywords: Late Antique art; Early Christian art; Bellerophon; Hinton St. Mary; Frampton; Lallingstone; ancient heroes in early Christian art